Responsive Parenting Buffers the Impact of Maternal PTSD on Young Children - Greene, Carolyn A. (Parent Sci Pract, 2020)
OBJECTIVE: This study investigates maternal responsive parenting behaviors as a theorized buffer to the detrimental impact of maternal PTSD symptoms on young children’s depression and anxiety symptoms, disruptive behavior, and stress-related symptoms. DESIGN: A multi-ethnic sample of 242 trauma-exposed mothers and their preschool-aged children was assessed. Maternal responsive parenting behaviors were observed during standardized parent-child interactions. Maternal and child mental health symptoms were reported by mothers. RESULTS: Maternal PTSD symptoms were associated with their responsive parenting behaviors and predicted children’s mental health symptoms. Responsive parenting was inversely associated with children’s depression and stress-related symptoms. Moderation analyses revealed an interactive effect of maternal symptoms and responsive parenting on preschool children’s disruptive behavior and stress-related symptoms. CONCLUSIONS: Responsive parenting behaviors can mitigate the ill effects of maternal PTSD symptoms. Nurturing relationships buffer the impact of maternal PTSD. Helping parents’ to sensitively respond to their young children’s distress can support positive outcomes in children.